Diplomasi Paralel Yogyakarta terhadap Victoria, Australia dalam Pelestarian dan Pengembangan Warisan Budaya Daerah - Jannah, Fajar Nur Roudhotul; Azmi, Fuad (Intermestic: Journal of International Studies, 2025)
The purpose of this research is to analyze the parallel diplomacy activities by DIY towards Victoria, Australia in the preservation and development of local cultural heritage. Local cultural heritage plays an important role in strengthening the identity of a region and can be used as an opportunity for cooperation. DIY, which is known as the center of Javanese culture, is aware of this potential and strives to preserve and develop cultural heritage by utilizing international networks, namely parallel diplomacy. The concept of parallel diplomacy used in this research makes the foreign actions taken by DIY legitimate in the national and international law. The approach used in this research is qualitative with interview techniques and document studies. The findings obtained from this research show that DIY's parallel diplomacy does not only introduce local culture to global parties, but also strengthens relationships between actors and produces concrete cooperation in the context of preserving and developing local cultural heritage.